2010
DOI: 10.1371/journal.pone.0010643
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Wound Healing by mTOR Activation in Genetically Defined Mouse Models

Abstract: BackgroundThe management of slow or non-healing ulcerations constitutes an increasing clinical challenge in the developed world because of the ageing of the population and the pandemic rise in type II diabetes. Recent studies suggest that molecular circuitries deployed by tumor cells to promote cancerous growth may also contribute to tissue regeneration. Here, we exploited this emerging information to search for novel molecular targets to accelerate wound healing.Methodology/Principal FindingsWe found that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
168
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(176 citation statements)
references
References 42 publications
(54 reference statements)
8
168
0
Order By: Relevance
“…These data suggest that different extracellular stimuli require various degrees of threshold Akt kinase activity for signaling. Furthermore, our findings in this study also connect well with those in several recent reports showing that the downstream effect of Akt, the mTOR pathway, plays an essential role in wound healing (33)(34)(35)(36)(37)(38). Therefore, taking all this together, it is becoming clear that the eHsp90␣-subdomain II of LRP-1-NPVY motif-Akt1/2-mTOR pathway represents a new therapeutic target for skin wound healing.…”
Section: Discussionsupporting
confidence: 90%
“…These data suggest that different extracellular stimuli require various degrees of threshold Akt kinase activity for signaling. Furthermore, our findings in this study also connect well with those in several recent reports showing that the downstream effect of Akt, the mTOR pathway, plays an essential role in wound healing (33)(34)(35)(36)(37)(38). Therefore, taking all this together, it is becoming clear that the eHsp90␣-subdomain II of LRP-1-NPVY motif-Akt1/2-mTOR pathway represents a new therapeutic target for skin wound healing.…”
Section: Discussionsupporting
confidence: 90%
“…Although not well defined functionally at this point, Akt has been shown to be activated and important for wound repair (Squarize et al, 2010). Previously, we have shown that gap-junctional communication within the first 6 hours post wounding is crucial for migration of primary human keratinocytes to fill the wounded region (Richards et al, 2004), so S373 phosphorylation might occur to increase communication in this time frame.…”
Section: Discussionmentioning
confidence: 93%
“…Constitutively active Akt repressed miR-199a-5p expression and was associated with accumulation of miR-199a-5p target HIF-1␣ (8). Given the fact that activation of both HIF (56,57) and Akt (58,59) takes place in the early stage of skin wound healing, it is tempting to speculate that these two pathways might act simultaneously to suppress miR-199a-5p expression, resulting in derepression of Ets-1 and enabling wound angiogenesis in a MMP-1-dependent mechanism. Further investigation is required to characterize the upstream stimuli in regulating the wound-associated down-regulation of miR-199a-5p.…”
Section: Discussionmentioning
confidence: 99%